Determining dominant process parameters in polyester yarn winding - Syahrul Ramadhan, A. K. A.; Jasri, Mohamad; Bazli, M. A. (Scientific Academia, 2020)
The manufacturing of spiral conveyor starts from yarn winding process in which the monofilament yarn is wounded around a hot mandrel mold to produce a spiral yarn. Due to several process parameters, the formation of the spiral’s diameter size can be inconsistent. Thus, it is important to determine the most dominant process parameter that affects the diameter of the formed spiral. In this study, design of experiment based on Taguchi method is used to investigate several parameters effect on the formation of spiral fabric. The investigation is based on the accuracy of the major and minor dimension of spirals being produced according to the specified dimension for several different factors and levels of the process parameters. It is found that process tension is the main parameter that affects the accuracy of the major dimension and the second heater gap is the main parameter that affect the accuracy of the minor dimension. In conclusion, these two process parameters need to be properly controlled to ensure good quality spiral is produced during the yarn spiral winding process.